Optimal Testing Choice and Diagnostic Strategies for Latent Tuberculosis Infection Among US-Born People Living with Human Immunodeficiency Virus (HIV). (6th August 2020) - Pettit, April C; Stout, Jason E; Belknap, Robert; Benson, Constance A; Séraphin, Marie Nancy; Lauzardo, Michael; Horne, David J; Garfein, Richard S; Maruri, Fernanda; Ho, Christine S; ,
Abstract: Background: Increased risk of progression from latent tuberculosis infection (LTBI) to tuberculosis (TB) disease among people living with human immunodeficiency virus (HIV; PLWH) prioritizes them for LTBI testing and treatment. Studies comparing the performance of interferon gamma release assays (IGRAs) and the tuberculin skin test (TST) among PLWH are lacking. Methods: We used Bayesian latent class analysis to estimate the prevalence of LTBI and diagnostic characteristics of the TST, QuantiFERON Gold In-Tube (QFT), and T.SPOT-TB (TSPOT) among a prospective, multicenter cohort of US-born PLWH ≥5 years old with valid results for all 3 LTBI tests using standard US cutoffs (≥5 mm TST, ≥0.35 IU/mL QFT, ≥8 spots TSPOT). We also explored the performance of varying LTBI test cutoffs. Results: Among 1510 PLWH (median CD4+ count 532 cells/mm 3 ), estimated LTBI prevalence was 4.7%. TSPOT was significantly more specific (99.7%) and had a significantly higher positive predictive value (90.0%, PPV) than QFT (96.5% specificity, 50.7% PPV) and TST (96.8% specificity, 45.4% PPV). QFT was significantly more sensitive (72.2%) than TST (54.2%) and TSPOT (51.9%); negative predictive value of all tests was high (TST 97.7%, QFT 98.6%, TSPOT 97.6%). Even at the highest cutoffs evaluated (15 mm TST, ≥1.00 IU/mL QFT, ≥8 spots TSPOT), TST and QFT specificity was significantly lower than TSPOT. Conclusions: LTBI prevalence among this cohort of US-born PLWH was low compared to non-US born persons. TSPOT's higher PPV may make it preferable for testing US-born PLWH at low risk for TB exposure and with high CD4+ counts. Abstract : Latent tuberculosis infection prevalence was low among this cohort of US-born persons .5 years old living with human immunodeficiency virus (HIV). T-SPOT.TB was more specific than the tuberculosis skin test or QuantiFERON Gold in-tube, resulting in fewer false positives.